Histiocytic necrotizing lymphadenitis with central nervous system involvement in children: An analysis of clinical features - Xiaoyuan Wu; Fang Guo; Yanhong Jia; Wenjun Luan; Chunxia Yang (Pakistan Journal of Medical Sciences, 2026)
Objective: To summarize the clinical features of histiocytic necrotizing lymphadenitis (HNL) with central nervous system (CNS) involvement in children. Methodology: A retrospective analysis was conducted on the clinical data of HNL-CNS children initially diagnosed and treated in Hebei Children’s Hospital from January 2015 to January 2025. Results: A total of 22 HNL-CNS children were enrolled, including 17 boys and 5 girls, with 16 children aged 6-12 years, of which 12 were boys. Fever and lymph node enlargement occurred in all 22 children, of which 17 (77.3%) suffered from headache and vomiting, 6 (27.3%) from convulsions, 4 (18.2%) from disorders of consciousness and 2 from status epilepticus. Eight children initially presented with neurological symptoms, and 4 exhibited recurrences. Reduced white blood cell (WBC) count was detected in 15 (68.2%) children, decreased hemoglobin (Hb) in 7 (31.8%) children, and increased alanine aminotransferase (ALT) in 12 (54.5%) children. There were 11 (50.0%) children with an anti-Mycoplasma pneumoniae (MP) antibody titer ≥ 1 : 160, 2 (9.1%) with Epstein-Barr (EB) viral DNA-positive, and 6 (27.3%) with autoantibody-positive. All the 22 children underwent lumbar puncture, revealing elevated cerebrospinal fluid (CSF) pressure in 18 (81.8%) children, elevated CSF WBC count (20-529 × 106/L, mainly monocytes) in 19 (86.4%) children, increased CSF proteins (0.42-2.45 g/L) in 11 (50.0%) children, and mostly normal glucose and chloride levels in CSF. Cranial magnetic resonance imaging (MRI) showed abnormalities in 15 children, among whom 8 (36.4%) children exhibited lesions located in the cerebral hemisphere, mostly in the frontal and occipital lobes, and 3 had leptomeningeal enhancement. The results of lymph node biopsy all met the typical changes of HNL. Antiviral therapy with acyclovir was given to 19 (86.4%) children, antibiotics were used in 17 (77.3%) children, intravenous corticosteroid (CS) therapy was provided to 19 (86.4%) children, and CSs combined with intravenous immunoglobulin (IVIG) was adopted in 8 (36.4%). Two out of three children who did not use CSs experienced recurrences. Conclusion: HNL-CNS occurs predominantly in school-age boys. Neurological symptoms may precede lymphadenopathy. CSF findings are characterized by elevated pressure and mononuclear pleocytosis. MRI lesions commonly involve frontal and occipital lobes. Corticosteroid therapy yields favorable clinical outcomes and a low recurrence risk.